FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL CONSUMER GOODS YANG TERDAFTAR DI BEI - RICKY SUGIANTO; Agustinus Sri Wahyudi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to test the factors that influence the company's capital structure. The independent variables in this study consist of Dividend policy, liquidity, tangibility, asset turnover and company growth. The data for this research are Consumer Goods listed on the Indonesia Stock Exchange (IDX) for the period 2015 to 2020. This study uses 66 samples and the sample selection procedure used is the purposive sampling method. This research test uses multiple regression analysis. Based on the results of the analysis, it can be concluded that Dividend policy has negative effect on capital structure. Company growth has positive effect on Capital structure. Liquidity, tangibility and asset turnover have no effect on Capital structure